Idiopathic Myocardial Fibrosis in Captive Chimpanzees (Pan troglodytes). Issue 1 (January 2020) - Strong, Victoria; Moittié, Sophie; Sheppard, Mary N.; Liptovszky, Matyas; White, Kate; Redrobe, Sharon; Cobb, Malcolm; Baiker, Kerstin
Cardiovascular disorders and predominantly idiopathic myocardial fibrosis are frequently associated with mortality among zoo-housed chimpanzees ( Pan troglodytes ). Formalin-fixed whole hearts of deceased chimpanzees housed in zoos ( n = 33) and an African sanctuary ( n = 2) underwent detailed macroscopic and histopathologic examination using a standardized protocol. Archived histological slides from the hearts of 23 additional African sanctuary-housed chimpanzees were also examined. Myocardial fibrosis (MF) was identified in 30 of 33 (91%) of the zoo-housed chimpanzees but none of the 25 sanctuary-housed chimpanzees. MF was shown to be characterized by both interstitial and replacement fibrosis. Immunophenotyping demonstrated that the fibrotic lesions were accompanied by the increased presence of macrophages, alpha smooth muscle actin-positive myofibroblasts, and a minimal to mild T-cell-dominant leukocyte infiltration. There was no convincing evidence of cardiotropic viral infection or suggestion that diabetes mellitus or vitamin E or selenium deficiency were associated with the presence of the lesion. However, serum vitamin D concentrations among zoo-housed chimpanzees were found to be lower in seasons of low ultraviolet light levels.